The Role of Flexibility and Competence on Work Performance According to the Mediating Role of Job Satisfaction Among Young Teachers in Sistan and Baluchistan Province - Otaki, Hamid; Rahdarpour, Javad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The most important task of education in this era, considering the complexity and expansion of science, is to first improve the performance of teachers and managers and to set precise targets to measure their performance. The present study was conducted with the aim of investigating the role of flexibility and competence on work performance with regard to the mediating role of job satisfaction among young teachers in Sistan and Baluchistan province. Methods: In terms of the purpose it was an applied study, the in terms of data collection it was a survey and it was a descriptive- correlation study. the statistical population was 440 young teachers of Sistan and Baluchistan province, who were selected using the Cochran formula and random sampling method. Multi-stage cluster, 205 people were selected as the sample size. Library and field data collection methods and tools for measuring written documents and four questionnaires, including Martin et al.’s human resources flexibility questionnaire (2005), Motahrinejad and Jahangard’s teacher competence questionnaire (2017) and Patterson’s occupational performance questionnaire (1922). Minnesota Job Satisfaction Questionnaire (MSQ) was used among teachers. The validity of the tool was measured through face, content and construct validity, and reliability was measured through Cronbach’s alpha and composite reliability. Structural equation modeling method was used for data analysis using SPSS-v23 and Smart Pls-v3 software. Results: The results showed that flexibility and competence have a significant effect on work performance according to the mediating role of job satisfaction among young teachers in Sistan and Baluchistan province. Conclusion: The results of the research showed that examining the role of job flexibility and competence on the work performance of young teachers with the mediation of job satisfaction can lead to efficient and satisfactory performance in the field of education.